EVALUATION OF STRATEGIC RISKS IN THE ACTIVITIES OF ENTERPRISE IN THE PROCESS OF BUSINESS PLANNING - BABII, Iryna; ZDRENYK, Vasyl; KOSIIUK, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the relevance of identifying and assessing strategic risks in business planning in conditions of uncertainty in the environment of the enterprise's functioning, and examines the essence and nature of threats and risks. It has been proven that modern business conditions require constant monitoring of risk-generating factors to create an effective and flexible system of business planning of an enterprise in conditions of instability. The typology of risks was studied, their varieties were characterized, and a diagram of their interaction was constructed. The article establishes that strategic risk management is an integral part of drawing up and implementing an enterprise's business plan. Features of analysis and assessment of preventable risks, strategic risks and internal risks in the process of business planning are considered. The authors provide an example of assessing the strategic risks of project implementation within the business plan. Using the example of the researched enterprise, the article highlights separate groups of project implementation risks in the business planning process. Based on the method of expert assessments, the average probability of occurrence of a particular type of risk was calculated as the arithmetic mean of the probabilities according to the opinions of three experts, as well as the total assessment of each type of risk taking into account the average weight of the risk of the implementation of the new project.The stages of assessing the consistency of experts' opinions using the mathematical method of calculating the concordance coefficient are presented and detailed. On the example of the researched enterprise, it was established that the risks of each group can have a different impact on the implementation of the project, therefore, the measures developed in the future for their prevention will be determined by the factors of the external and internal environment. It is summarized that the effectiveness of business planning and the effectiveness of the activities of economic entities largely depend on the adopted method of risk assessment.
Keywords: enterprise management; risk; business planning; strategic planning